2016
DOI: 10.1111/1365-2656.12583
|View full text |Cite
|
Sign up to set email alerts
|

How individual Montagu's Harriers cope with Moreau's Paradox during the Sahelian winter

Abstract: Summary 1.Hundreds of millions of Afro-Palaearctic migrants winter in the Sahel, a semi-arid belt south of the Sahara desert, where they experience deteriorating ecological conditions during their overwintering stay and have to prepare for spring migration when conditions are worst. This well-known phenomenon was first described by R.E. Moreau and is known ever since as Moreau's Paradox. However, empirical evidence of the deteriorating seasonal ecological conditions is limited and little is known on how birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 46 publications
1
63
2
Order By: Relevance
“…Harriers breeding in western Europe spend the wintering season (October-March) in the western Sahel (Limiñana et al 2012, Trierweiler et al 2013, where they prey mostly on grasshoppers (Trierweiler and Koks 2009, Trierweiler et al 2014, Augiron et al 2015, Schlaich et al 2016. The Montagu's harrier is a long-distance migrant breeding across the open farming landscapes of the western Palearctic, from northern Morocco to western Russia and Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…Harriers breeding in western Europe spend the wintering season (October-March) in the western Sahel (Limiñana et al 2012, Trierweiler et al 2013, where they prey mostly on grasshoppers (Trierweiler and Koks 2009, Trierweiler et al 2014, Augiron et al 2015, Schlaich et al 2016. The Montagu's harrier is a long-distance migrant breeding across the open farming landscapes of the western Palearctic, from northern Morocco to western Russia and Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…bees, fish in small ponds, birds), lifelong tracking of individuals (e.g. using RFID and satellite tracking; see Case study 1 [27]) is already possible. Information on individual variation in circadian organization, in combination with data on longevity will provide new insights on the evolutionary consequences of daily rhythms in free-ranging animals (table 1, question 5).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this particular example, activity patterns tended to be similar across individuals at a given site, but varied to a greater degree across sites (figure 2), possibly suggesting a prominent role of environmental drivers shaping activity patterns in wild Montagu's Harriers. Seasonal differences in daily activity patterns could, for instance, arise from different feeding habits of Montagu's Harriers in the three different seasons: voles and the need to feed young during the breeding season [57], eggs and nestlings of passerines during the main spring stopover in northwest Africa [27], and grasshoppers in winter [44]. Whether between-individual variation in activity patterns reflects differences in individual personalities, with some birds being more explorative than others (e.g.…”
Section: (B) Diel Activity Patterns Of Diurnal Raptorsmentioning
confidence: 99%
“…Song birds and insectivorous raptors in the habitat of higher food availability and more rainfall depart earlier than those in the habitat of lower food availability and less rainfall3637. The NDVI has been used to represent the ecological and habitat conditions of wintering and stopover habitats to predict the migration dates of terrestrial insectivorous birds141838.…”
Section: Discussionmentioning
confidence: 99%
“…that the importance of the NDVI during the entire wintering stay was confounded by the strong effect of year in their study. Schlaich et al 37. found that Montagu’s harriers ( Circus pygargus ) increased flying and foraging time in the habitat of low NDVI and grasshopper (prey) abundance and subsequently delayed spring departures from the wintering grounds in the Sahel.…”
Section: Discussionmentioning
confidence: 99%